The Listeria Small RNA Rli27 Regulates a Cell Wall Protein inside Eukaryotic Cells by Targeting a Long 5′-UTR Variant - Quereda, Juan J. (Public Library of Science, 2014)
Listeria monocytogenes is a bacterial pathogen whose genome encodes many cell wall proteins that bind covalently to peptidoglycan. Some members of this protein family have a key role in virulence, and recent studies show that some of these, such as Lmo0514, are upregulated in bacteria that colonize eukaryotic cells. The regulatory mechanisms that lead to these changes in cell wall proteins remain poorly characterized. Here we studied the regulation responsible for increased Lmo0514 protein levels in intracellular bacteria. The amount of this protein increased markedly in intracellular bacteria (>200-fold), which greatly exceeded the increase in lmo0514 transcript levels (∼6-fold). Rapid amplification of 5′-cDNA ends (RACE) assays identified two lmo0514 transcripts with 5′-untranslated regions (5′-UTR) of 28 and 234 nucleotides. The transcript containing the long 5′-UTR is upregulated by intracellular bacteria. The 234-nucleotide 5′-UTR is also the target of a small RNA (sRNA) denoted Rli27, which we identified by bioinformatics analysis as having extensive base pairing potential with the long 5′-UTR. The interaction is predicted to increase accessibility of the Shine-Dalgarno sequence occluded in the long 5′-UTR and thus to promote Lmo0514 protein production inside the eukaryotic cell. Real-time quantitative PCR showed that Rli27 is upregulated in intracellular bacteria. In vivo experiments indicated a decrease in Lmo0514 protein levels in intracellular bacteria that lacked Rli27. Wild-type Lmo0514 levels were restored by expressing the wild-type Rli27 molecule but not a mutated version unable to interact with the lmo0514 long 5′-UTR. These findings emphasize how 5′-UTR length affects regulation by defined sRNA. In addition, they demonstrate how alterations in the relative abundance of two transcripts with distinct 5′-UTR confine the action of an sRNA for a specific target to bacteria that occupy the intracellular eukaryotic niche.